1981
DOI: 10.1212/wnl.31.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Acute carbamazepine toxicity resulting from overdose

Abstract: Four patients with an acute overdose of carbamazepine were examined with serial blood level determinations. The clinical spectrum consisted of coma, respiratory depression, seizures, myoclonus, nystagmus, hyperreflexia, hyporeflexia, delayed gastric emptying with cyclic coma, ataxia, sinus tachycardia, and atrioventricular conduction delay. Carbamazepine elimination half-lives varied from 10 to 29 hours, and in one case carbamazepine-10,11-epoxide was measured and had a half-life of 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…33 The findings here draw particular attention to the importance of trust and personal relationships in inter-company relations for the Japanese. 34 The managing director and the general manager of Albion-Nippon, and the executive director of Chuan-Nippon drew attention to the critical importance of personal relationships for the Japanese. These managers would be expected to have intimate knowledge of, and be sensitive to, the needs and perceptions of the Japanese given the longevity of their relationship (around 10 years in the case of Albion-Nippon's managing director and general manager and more than three years for Chuan Group's executive director).…”
Section: Discussionmentioning
confidence: 99%
“…33 The findings here draw particular attention to the importance of trust and personal relationships in inter-company relations for the Japanese. 34 The managing director and the general manager of Albion-Nippon, and the executive director of Chuan-Nippon drew attention to the critical importance of personal relationships for the Japanese. These managers would be expected to have intimate knowledge of, and be sensitive to, the needs and perceptions of the Japanese given the longevity of their relationship (around 10 years in the case of Albion-Nippon's managing director and general manager and more than three years for Chuan Group's executive director).…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of either intentional or accidental (Smoot & Wood, 1977;De Zeeuw et al, 1979;Sullivan et al, 1981;Leslie et al, 1983) poisoning with carbamazepine have been reported; the main problems encountered were drowsiness progressing to coma, respiratory depression, convulsions and cardiac arrhythmias including sinus tachycardia, nodal bradycardia, conduction defects and heart block (Smoot & Wood, 1977;Hamilton, 1978;De Zeeuw et al, 1979;Sullivan et al, 1981;Leslie et al, 1983). Late toxicity has been reported (De Zeeuw et al, 1979;Sullivan et al, 1981) presumed due to delayed absorption from the gut (Sullivan et al, 1981). The recorded quantity of drug ingested varied from 1.2 g (Sullivan et al, 1981) to 20 g (Lehrman & Bauman, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Late toxicity has been reported (De Zeeuw et al, 1979;Sullivan et al, 1981) presumed due to delayed absorption from the gut (Sullivan et al, 1981). The recorded quantity of drug ingested varied from 1.2 g (Sullivan et al, 1981) to 20 g (Lehrman & Bauman, 1981). In most cases, no correlation was made with body weight but survival in adults has been reported after ingestion of carbamazepine 150 mg/kg (Smoot & Wood, 1977) and 200 mg/kg (Lehrman & Bauman, 1981) body weight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations